Public safety intelligence activity: Advice in the fight against criminal organizations (Research, Society and Development, 2021)
The present work, as a research involving the intelligence activity in Public Security, the present work aimed, through a historical rescue, which dates back to the emergence of a criminal organization in the state of Pará - Brazil, to verify how the intelligence activity it is capable of advising the decision-making process of public security institutions, in order to generate a balance of forces favorable to the latter, in the fight against crime. It started from the hypothesis that the intelligence agencies would show themselves capable of gathering privileged information, according to legality and efficiency criteria, able to subsidize the decision-making process. Using an inductive method and a qualitative documentary analysis, it was identified that, in addition to subsidizing managers with appropriate knowledge, the agencies were responsible for the frustration of measures of direct confrontation with the State, preventing damage to public coffers, as well as unjust attacks on civil and military civil servants and the Pará society itself.